1986
DOI: 10.1017/s0022215100099060
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic salivary tissue and branchial sinuses

Abstract: Heterotopic salivary tissue and branchial sinuses occur not infrequently (Goddman et al., 1981; Stingle and Priebe, 1974), caused probably by heteroplasia within remants of the second cleft (Stingle, 1974). Bilateral lesions which presented clinically as branchial cleft sinuses have been removed from a patient's neck; both of them proved to be branchial cleft sinuses with elements of slivary tissue.The paper describes sailvary tissue and branchial sinuses along the anterior border of the sternocleidomastoid mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…There were 9 bilateral cases [6,10,11,12,13,14,15,16]. A summary of these bilateral cases is presented in table 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 9 bilateral cases [6,10,11,12,13,14,15,16]. A summary of these bilateral cases is presented in table 1.…”
Section: Discussionmentioning
confidence: 99%
“…We found two characteristics common to bilateral cases. The first is family history: 4 patients had a family history of some cervical anomalies [10,12]. Hsu et al [10] reported familial occurrence of HSGT, representing an autosomal dominant inheritance pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tonsil, mandible, lower neck, hypopharynx, sternoclavicular joint or middle ear) [1], To our knowledge, only 23 cases of het erotopic salivary gland tissue in the neck have been reported up to 1986 [2,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…However, a primary connective tissue LELC could be assumed, based on the branchial embryonic remnants origin, particularly from branchial cysts arisen from the second branchial arch [21]. In fact, these cysts, consisting of lymphoid aggregates that can have either squamous or respiratory-type epithelial lining, occur mostly along the front edge of the sternocleidomastoid muscle from the plane passing through the hyoid bone to the suprasternal notch [21, 22, 23]. …”
mentioning
confidence: 99%